A Mouse Model to Evaluate the Impact of Species, Sex, and Lipid Load on Lymphatic Drug Transport - Trevaskis, Natalie L. (2013)
PURPOSE: To establish a lymph-cannulated mouse model, and use the model to investigate the impact of lipid dose on exogenous and endogenous lipid recruitment, and drug transport, into the lymph of males versus females. Finally, lymphatic transport and drug absorption in the mouse were compared to other pre-clinical models (rats/dogs). METHODS: Animals were orally or intraduodenally administered 1.6 mg/kg halofantrine in low or high (14)C-lipid doses. For bioavailability calculation, animals were intravenuosly administered halofantrine. Lymph or blood samples were taken and halofantrine, triglyceride, phospholipid and (14)C-lipid concentrations measured. RESULTS: Lymphatic lipid transport increased linearly with lipid dose, was similar across species and in male/female animals. In contrast, lymphatic transport of halofantrine differed markedly across species (dogs>rats>mice) and plateaued at higher lipid doses. Lower bioavailability appeared responsible for some species differences in halofantrine lymphatic transport; however other systematic differences were involved. CONCLUSIONS: A contemporary lymph-cannulated mouse model was established which will enable investigation of lymphatic transport in transgenic and disease models. The current study found halofantrine absorption and lymphatic transport are reduced in small animals. Future analyses will investigate mechanisms involved, and if similar trends occur for other drugs, to establish the most relevant model(s) to predict lymphatic transport in humans.